Hypidone Hydrochloride (YL-0919) Produces a Fast-Onset Reversal of the Behavioral and Synaptic Deficits Caused by Chronic Stress Exposure - Ran, Yuhua; Jin, Zengliang; Chen, Xiaofei; Zhao, Nan; Fang, Xinxin; Zhang, Liming; Zhang, Youzhi; Li, Yunfeng (Frontiers in Cellular Neuroscience, 2018)
Our previous study showed that hypidone hydrochloride (YL-0919), a partial serotonin 1A (5-HT1A) receptor agonist and 5-HT reuptake inhibitor, exerts a significant antidepressant effect in various animal models. The aim of the present study was to further investigate the underlying mechanisms and whether it could act as a fast-onset antidepressant. In the current study, depressive-like behavior was induced in rats by a chronic unpredictable stress (CUS) model and assessed with the Sucrose Preference Test (SPT). Treatment with YL-0919 (2.5 mg/kg, i.g.), but not with fluoxetine (Flx; 10 mg/kg, i.g.), caused a fast improvement in the SPT scores. In CUS-exposed rats, YL-0919 treatment for 5 days decreased the immobility time in a forced swimming test (FST), and a 10-day treatment decreased the latency to feed in a Novelty-Suppressed Feeding Test (NSFT). In addition to the behavioral tests, the effects of YL-0919 on synaptic protein expression were also evaluated. Western blotting showed that YL-0919 significantly enhanced the expression levels of synaptic proteins such as synapsin I, postsynaptic density protein 95 (PSD95), phosphorylated mammalian targeting of rapamycin (pmTOR) and brain-derived neurotrophic factor (BDNF) in the hippocampus. To determine how the mTOR signaling is involved in the fast-onset antidepressant-like effects of YL-0919, the mTOR-specific inhibitor rapamycin was administered intracerebroventricularly (i.c.v.) together with the YL-0919 treatment. The observed changes in behavioral tests and protein expression could be reversed by rapamycin treatment. This suggests that the fast-onset antidepressant effects of YL-0919 were partially caused by changes in synaptogenesis mediated by activation of mTOR pathways. Our data suggest that YL-0919 may be a powerful/effective antidepressant with fast-onset.